The effect of prolongation in various suppressor tone to Transient Evoked Otoacoustic Emission (TEOAE) suppression - Mohd Nawawi, Nur Izzati; Dzulkarnain, Ahmad Aidil Arafat (2012)
Otoacoustic emission (OAE) suppression is an objective, and non-invasive clinical test that has been used to study the efferent central auditory nervous system pathways. This study was conducted to understand the pattern of OAE suppression if prolonged contralateral acoustic stimulation is given over different type of suppressor. The major aim of this study was to compare the suppression of Transient Evoked Otoacoustic Emission (TEOAE) recorded using different suppressor tones that were prolonged in duration at various intervals. Fifty normal hearing adult’s subjects (23.04 ± 1.30year old) (with total of 100 ears) were involved in this study. Qualified subjects undergone TEOAE test using 100 microseconds monophasic clicks (at 84 dBpe SPL) in 4 different phases: (i) baseline with no suppressor at contralateral ear, (ii) TEOAE suppression with suppressor at contralateral ear after 1 minutes, (iii) TEOAE suppression with suppressor at contralateral ear after 3 minutes, (iv) TEOAE suppression with suppressor at contralateral ear after 5 minutes and (v) TEOAE post- noise exposure recording. Two types of suppressor were used in this study, (i) 65 dB SPL narrowband noise (NBN) and (ii) 65 dB SPL warble tone (WB) at 1 kHz. Results showed that the NBN and WB tones gave an average suppression of 0.845 ± 1.4 dB and 0.448 ± 2.1 dB respectively from the baseline to 1 minute of noise exposure. This value however is smaller compared to at least minimum of 1 dB SPL suppression when using white (Collet, 1993) when using white noise. This different might be contributed by the widespread of the energy spectrum in white noise compared to both NBN and WB suppressor. In addition, Repeated Measure ANOVA (RM ANOVA) analysis at 95% confidence level showed that the TEOAE amplitude was significantly reduced (p < 0.05) as the duration of NBN masker increased, however there was no significant changes (p > 0.05) in the TEOAE amplitude at different phases while using WB tone. The TEOAE suppression result recorded using NBN and WB is not consistent with the 1-4 dB reduction of TEOAE suppression using white noise (Berlin et al., 1994, Collet et al., 1992, Veuillet et al., 1992). This difference might be due to the wide frequency spectrum in white noise masker (20 to 20 000 Hz) which enable them to inhibit majority of the OHC thus suppress the majority of OAE energy. Next, the TEOAE absolute amplitude in post noise exposure was compared using paired t-test. The results revealed that the TEOAE amplitude was significantly higher (p>0.05) in post noise exposure compared to the baseline recording which indicates outer hair cells sensitivity was increase after prolonged contralateral noise (Zyl A et al., 2008). In general, this study concluded that the NBN and WBN have the same effect as white noise suppressor when the duration of the suppressor tone is increased, thus this study should be expand to pathological populations to see if there is clinical values behind it.